Caveat Manipulator: (Re)forming Geographic Information Systems - Fromme, Tres (UnderCurrents: Journal of Critical Environmental Studies, 1996)
Geographic Information Systems (GIS) have, within the last few years, engaged the interests of academics and professionals in the many fields- cartography, geography, computer remote sensing, and among others-at whose intersection GIS emerges. An acknowledged limited survey of the writings and issues indicates that much of the material concentrates on methods, technologies, and applications. The dominant tone of the research and work is positivistic and rareified, as if GIS existed outside of any social situation. Writers enthusiastically concern themselves with data models, (hard/soft)ware issues, and quantifiable results and measures. [...]